Analisis Efektivitas Dan Efisiensi Pengelolaan Keuangan Daerah Pada Sekretariat Daerah Kabupaten Lima Puluh Kota - Yezi Hidayati; Helmi Ali (Jurnal Mirai Management, 2023)
This research is a descriptive study, at the X Regency Government with the title: Analysis of the Effectiveness and Efficiency of Regional Financial Management at the Regional Secretariat of Regency X. The purpose of this study was to determine the level of efficiency and effectiveness of regional financial management in terms of the use of funds and revenues from the Regional Secretariat. The analytical tool used to determine the implementation of financial management of the Regional Secretariat is, with a descriptive description which includes; data presentation, and conclusion drawing / verification. Meanwhile, to determine the level of effectiveness and efficiency of regional financial management, using the efficiency ratio and effectiveness ratio. The results of the financial management efficiency analysis show that the calculation of the overall efficiency level formulation averaged in the last 3 years from 2020 - 2022 is 93.02%, this shows that the efficiency level is still low because the results are less than 100%. This shows that the regional secretariat is still not maximizing in using its budget. The results of the analysis of the effectiveness of the financial management of the regional secretariat show that the calculation of the formulation of the level of effectiveness of the financial management of the regional secretariat from 2020 to 2022 fluctuates with the level of effectiveness, this is also influenced by the covid 19 pandemic, where revenue is reduced.